As contribuições do curso de administração de empresas na atitude empreendedora dos seus discentes: o caso da faculdade OPET - Pereira, Adriano Toledo (2006)
Scholar’s entrepreneurial attitudes show business administration bachelor’s degree course contributions. The study intends to verify perceived contributions based on the course structure, its classes and projects. A field research in a college located in Curitiba was conducted to prove the effectiveness of these contributions. Three research typologies were accomplished to achieve the proposed purposes. The first one, a quantitative stage, a survey research was conducted with a sample of 378 business administration scholars in the OPET College. The second one was structured based on semi-structured interviews with the college’s principal, the course’s coordinator and professors. In the last one, the pedagogic project of the course and the classes appointments was been analyzed. Based on the entrepreneurial attitude evaluation methodology adopted and the business administration course contribution on the entrepreneurial education, results were analyzed to identifying prospecting and innovation attitudes, same as management and firmness. Results were also analyzed to distinguish the independent entrepreneurial and intrapreneurial attitudes. Quantitative stage shows that the course has a significant contribution to the scholars’ entrepreneurial attitudes adoption. These scholars intend to present more management and firmness attitudes than prospecting and innovation ones. Intrapreneurial attitudes were more frequent in relation to the independent entrepreneurial attitudes. Semi-structured interviews results seem to show the high meaning of an entrepreneurial education. However, few actions are developed to increase the entrepreneurial attitudes of the scholars, what shows that is not the college focus. Analyzing the pedagogic project and the classes appointments was not found any specific mention to the entrepreneurial education. Considering this scenario, the study proposes some recommendations to the scholars’ entrepreneurial education strengthening, which will be evaluated and possibly implemented by OPET College.